2015
DOI: 10.1016/j.bbmt.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy and Sigmoidoscopy are Equally Effective for the Diagnosis of Colonic Acute Graft-versus-Host Disease in Patients with Diarrhea after Allogeneic Stem Cell Transplantation: A Prospective Controlled Trial

Abstract: Colonic acute graft-versus-host disease (aGVHD) affects approximately 10% of patients who have undergone allogeneic stem cell transplantation (allo-SCT). Diarrhea is a major clinical sign but also a common post-transplantation symptom in these patients. Comprehensive histopathologic examination of the colon is therefore regarded as crucial to establish a diagnosis, but the colonic segment that should be targeted for a diagnostic biopsy remains a topic of debate. The primary objective of this study was to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Most of the studies support rectosigmoid biopsies, given their high sensitivity (82%-95%) regardless of the symptom profile. 11,12 In hemopoeitc stem cell transplant patients with diarrhea, colonoscopy and sigmoidoscopy are equivalent in diagnosing GVHD, so the latter may benefit patients with a high procedural risk. 12 Endoscopically, GVHD displays erythema, edema, erosions, and denudation of mucosa; however, approximately half of patients with normal colonoscopies and 60% with normal EGDs had histologic evidence of GVHD-strongly supporting obtaining biopsies irrespective of normal-appearing mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies support rectosigmoid biopsies, given their high sensitivity (82%-95%) regardless of the symptom profile. 11,12 In hemopoeitc stem cell transplant patients with diarrhea, colonoscopy and sigmoidoscopy are equivalent in diagnosing GVHD, so the latter may benefit patients with a high procedural risk. 12 Endoscopically, GVHD displays erythema, edema, erosions, and denudation of mucosa; however, approximately half of patients with normal colonoscopies and 60% with normal EGDs had histologic evidence of GVHD-strongly supporting obtaining biopsies irrespective of normal-appearing mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In hemopoeitc stem cell transplant patients with diarrhea, colonoscopy and sigmoidoscopy are equivalent in diagnosing GVHD, so the latter may benefit patients with a high procedural risk. 12 Endoscopically, GVHD displays erythema, edema, erosions, and denudation of mucosa; however, approximately half of patients with normal colonoscopies and 60% with normal EGDs had histologic evidence of GVHD-strongly supporting obtaining biopsies irrespective of normal-appearing mucosa. 13 Chimerism or the presence of donor lymphocytes in the patient's peripheral blood can confirm clinical suspicion of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, there was a report describing the usefulness of magnifying endoscopy for the terminal ileum 19 . However, recent studies indicated that the rectosigmoidoscopy is sufficient for diagnosing gastrointestinal GVHD 8 10 11 12 . It could be ideal to scope up to the proximal colon or the ileum to identify the activity of GVHD more precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have reported that a biopsy from the lower intestinal tract has equal or superior sensitivity for the pathological diagnosis of gastrointestinal GVHD compared to a biopsy from the upper gastrointestinal tract 4 5 6 7 8 9 . Furthermore, some studies reported that a biopsy from the rectosigmoid portion, rather than from the right colon or the ileum, is sufficient for diagnosis 8 10 11 12 . Since upper GI endoscopy and total colonoscopy are more invasive than rectosigmoidoscopy, rectosigmoidoscopy with biopsy has been regarded as the more useful way to diagnose gastrointestinal GVHD in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible sigmoidoscopy is as sensitive as full colonoscopy. [19] Upper GI endoscopy is often performed, as the small bowel may be the major source of diarrhea, although this approach is not universally accepted. [20] Although GI GVHD symptoms may start as early as 9 days after HCT, they often do not start until patients have been discharged from the hospital, and accurate measurements of outpatient diarrheal output are not routinely available.…”
Section: Diagnosismentioning
confidence: 99%